Effect Logical Relatedness and Semantic Overlap on Argument Evaluation. Issue 7 (2nd October 2016) - Dandotkar, Srikanth; Magliano, Joseph P.; Britt, M. Anne
Abstract : In two studies we examined the extent to which skilled and less-skilled reasoners of arguments relied on relevance relations (semantic and logical relatedness) between claims and reasons when evaluating arguments. College students, selected as having high or low analytical reasoning skill, evaluated the quality of a set of two sentence arguments and rated the strength of their agreement with them. The arguments were structured to vary in their degree of semantic and logical relatedness. Experiment 1 used a direct test of readers' evaluation of the logical connection, whereas Experiment 2 used a more naturalistic, multifactor task (agreement judgment). Overall, both skilled and less-skilled reasoners accepted and more strongly agreed with high logical arguments than they did with low logical arguments, indicating that both skilled and less-skilled reasoners rely more on logical relatedness when evaluating arguments. However, skilled reasoners' reliance on logical relatedness was higher than that of less-skilled reasoners', particularly when evaluating the quality of and not their strength of agreement with arguments. With respect to semantic relatedness, readers' reliance on this factor was minimal across experiments. Contrary to the findings in the narrative comprehension research, less-skilled reasoners did not excessively rely on semantics under low logical conditions. In fact, skilled evaluators relied on semantics more when evaluating the quality of high logical arguments. Finally, the current studies confirm the earlier findings that precision in remembering the main verb of the claim is fundamental to one's skill in evaluating arguments.